PENGENALAN AUDIT KEUANGAN SEBAGAI PILAR PEMBENTUKAN KEPEMIMPINAN YANG TRANSPARAN DAN BERTANGGUNG JAWAB KEPADA SISWA SMAN 2 PANDEGLANG (TRIDAYA: Jurnal Pengabdian kepada Masyarakat, 2025)
This community engagement initiative introduces basic principles of financial auditing as a strategic effort to cultivate leadership characterized by transparency and accountability among student organizations and extracurricular bodies at SMAN 2 Pandeglang. The program is implemented through a structured educational activity aimed at improving students’ awareness of how financial audits function in supervising, recording, and evaluating organizational financial activities within a school context. The delivered materials address key topics such as an overview of financial statements, fundamental auditing concepts, basic audit procedures, and how audit mechanisms reinforce leadership values like integrity, accountability, and openness. By participating in this activity, students are expected to adopt and apply these values when managing student organization finances, thereby supporting the growth of ethical leadership practices within the school environment.